Corroboration of Normalized Least Mean Square Based Adaptive Selective Current Harmonic Elimination in Voltage Source Inverter using DSP Processor - P. Avirajamanjula; P. Palanivel (Institute of Advanced Engineering and Science, 2015)
A direct Selective current harmonic elimination pulse width modulation technique is proposed for induction motor drive fed from voltage source inverter. The developed adaptive filtering algorithm for the selective current harmonic elimination in a three phase Voltage Source Inverter is a direct method to improve the line current quality of the Voltage Source Inverter base drive at any load condition. The self-adaptive algorithm employed has the capability of managing the time varying nature of load (current). The proposed Normalized Least Mean Squares algorithm based scheme eliminates the selected dominant harmonics in load current using only the knowledge of the frequencies to be eliminated. The algorithm is simulated using Matlab/Simulink tool for a three-phase Voltage Source Inverter to eliminate the fifth and seventh harmonics. The system performance is analyzed based on the simulation results considering total harmonic distortion, magnitude of eliminated harmonics and harmonic spectrum. The corroboration is done in the designed Voltage Source Inverter feeding induction motor using digital signal processor-TMS320L2812.The developed algorithm is transferred to digital signal processor using VisSimTM software.